A política do direito e o direito da política: lutas por poder e transformações do habitus do campo jurídico no Brasil República - Paula, Quenya Silva Correa de (2019)
The purpose of this study is to understand, in a given historical process, the formation and formatting of social structures that are prior and superior to the individuals themselves, in order to identify the cultural permanences that infer in lasting transformations. The idea of a living and relational space, of approximation and distance, allows us to know the past and imagine the future from the tensions exercised in the present. Political, economic, juridical and social forces move and articulate themselves through the "elitist habitus", acquired or incorporated in the process of school formation to produce, reproduce and perpetuate the dominant interests. The formation of the National State was discussed, fundamentally, from the authors of Weberian tradition, with the aim of highlighting the protagonism of the legal field in this formation, because, although strangled by the political and economic fields, its performance makes feasible and legitimizes the state's aspirations. On the other hand, the field of communication is relevant because it transmits the official discourse to society, hierarchically, vertically, sewn "top-down", creating a collective consciousness and ways of seeing social reality. The politics and history of Brazilian society are marked by cultural permanence, by a homogeneity of the ruling elites that, although they are replaced by new elites, do not alter the practices and the games of power. On the main stage, therefore, are the macrostructures of the analyzed fields, not the actors per se, who try to govern society under the justification of protecting it. Brazilian governments (from the Empire to the Republic) will be analyzed and their effects identified on the legal field, especially with regard to antidemocratic ruptures, since the Citizen Constitution was drafted with a view to guarantee the rights of society, seeking to protect it and to remove it from authoritarian governments. While the Eliasian theoretical-methodological model enables us to reconstitute and analyze the long-lived historical-social processes, the Bourdieusian theory makes it possible to keep up with the permanences, transformations and conflicting dynamics between the fields of power.